Fama and French risk factors constructed from Russell/Nomura style indexes: evidence from Japanese monthly and daily data sets - Lau, W.Y. (2009)
This paper uses risk factors constructed from Russell/Nomura style indexes as proxies in an attempt to make the Fama and French three-factor asset pricing model more appealing. The performance of these benchmark factors is evaluated through a direct and simple generalized method of moments test using both daily and monthly data sets of the 33 Japanese industry indexes. Our constructed Fama and French three risk factors can explain returns on most of the 33 industry indexes of all common stocks listed on Tokyo Stock Exchange First Section, JASDAQ, Hercules, and other exchanges. Moreover, the three factors risk premia finding confirms the conclusion concerning the nature of the reversal of the size effect.